Pengaruh Disiplin Kerja dan Lingkungan Kerja pada Kinerja Karyawan PT. Asia Fasifik Fiber Kendal - Ifanto, Feri; Suhana, Suhana (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of work discipline and the work environment on employee performance at PT. Asia Fasifik Fiber Kendal. Employee performance is a crucial factor in determining a company's success, therefore, discipline and a conducive work environment are essential to increase productivity. The research method used was a quantitative field approach, where data were collected through observation, interviews, and questionnaires distributed to employees at PT. Asia Fasifik Fiber Kendal. The research instrument was constructed using a Likert scale to measure the level of work discipline, work environment, and employee performance. The results showed that work discipline had a positive and significant effect on employee performance, meaning that the higher the level of employee discipline, the better the resulting performance. Furthermore, the work environment also had a positive and significant effect on employee performance. A comfortable, safe, and harmonious work environment has been shown to increase employee motivation and productivity. The conclusion of this study is that improving work discipline and improving the work environment simultaneously will encourage improved employee performance and contribute to the company's success in achieving organizational goals.   Keywords: Work Discipline, Work Environment, Employee Performance, Productivity